A Philosophical Appraisal of Prosperity Teaching in Selected Churches in Southwestern Nigeria (2014)
Prosperity teaching is the idea that health and wealth are compulsory benefits of the Christian faith. Most followers of this teaching have accepted it dogmatically, making them vulnerable to exploitation and delusion. Previous studies on prosperity teaching have examined it from hermeneutical and theological perspectives without sufficient attention paid to its appraisal from the philosophical viewpoint which is capable of providing a balanced understanding of prosperity teaching. This study, therefore, assessed prosperity teaching in terms of its principles, logicality, consistency with biblical teachings and effects on its followers. The study adopted Immanuel Kant‟s Principle of Humanity. Three Pentecostal churches; Living Faith: (LFC), Redeemed Christian Church of God (RCCG), and Livingspring Chapel (LSC) were purposively selected because prosperity teaching is more entrenched in their practices. Data were collected from books written by Bishop David Oyedepo, Pastor Enoch Adeboye and Pastor Femi Emmanuel. Additional information was collected from thirty tapes/DVDs on prosperity teaching. Forty members of selected churches were randomly interviewed (RCCG 15, LFC 15, LSC 10). Using the stratified random sampling technique, 640 copies of a questionnaire were administered to 440 members and 200 officers from two branches each of RCCG and LFC (Ogbomoso, Oyo, Lagos, Sagamu and Otta) and LSC (Ibadan). Data were subjected to philosophical analysis and percentages. Four basic principles of prosperity teaching were adopted at varying degrees of emphasis in the selected churches. While they all taught “wealth is a compulsory gain of salvation” and “positive confession attracts positive actions to believers”, RCCG and LSC emphasized “sowing fatly to reap multiple blessings”. LFC emphasized “Divine unfailing health is guaranteed to believers”. A critical evaluation however reveals the illogicality and inconsistency of prosperity teaching: “wealth as gain of salvation” fails to explain why Christians like Apostles Peter and John were poor (Acts 3:6). “Sowing and reaping” contradicts Jesus‟ directive to Christians to give, expecting nothing in return but to store treasures in heaven (Matt. 6:19). “Covenant of divine unfailing health” contradicts scientific and biblical proofs (I Tim. 5:20) of human‟s vulnerability to sickness. “Positive verbal confession” is hinged on a faulty premise of an anthropocentric view that humans are in God‟s class, making prayerful requests unnecessary. Besides, 80.0% interviewed from LFC accepted they occasionally fall sick despite assurances of “divine unfailing health” and 55.0% in RCCG agreed they were yet to reap from “kingdom investments”, negating the automation of “reaping from sowing”. A total of 85.0% respondents believed they attracted blessings from positive confession, agreeing in part with the “principle of verbal confession”, and 90.0% officers and members across selected churches believed they were rich. On the opposite, 70.0% members had no personal house(s), 63.0% had no personal car(s), 62.0% estimated their yearly income at less than N1m, contradicting the principle of “wealth as gain of salvation”. Although popularly accepted among selected churches, prosperity teaching is fideistic, negates Kant‟s Principle of Humanity and is inconsistent with biblical teachings and followers practical life experiences. Prosperity exponents should teach balanced theology that encourages rational faith for more effective Christian impacts.